FIRST RECORD OF KNEMIDOCOPTES MUTANS FROM CHICKEN IN IRAQ - O.AL-ANI, MUNTASIR; A.HASSAN, EMAD; A.SHALASH, ALI (The Iraqi Journal of Veterinary Medicine, 1996)
Knemidocoptes mutans (Sercoptidae) was recorded for the first time in IRAQ in egg laying fowl that have been kept on bad managment in house cages.